Fostering Islamic Accounting curriculum to achieve competitive advantage - Zahron Abdurrahman (Proceeding International Conference on Accounting and Finance, 2025)
Islamic based accounting education has lagged behind the rapid growth of Islamic finance and business sectors, creating a gap in the availability of qualified human resources needed to support the industry's expansion. This study proposes a conceptual model to identify and evaluate key factors that influence the implementation of Islamic accounting education in addressing labor market demands for both quantity and quality. The aim is to develop a comprehensive framework that encompasses the critical elements impacting the successful formula of Islamic accounting education curriculum within Higher Education Institutions (HEIs). The findings highlight major barriers, including limited institutional support, insufficient curriculum development, a shortage of qualified educators, low awareness of Islamic finance principles, and difficulties in harmonizing Islamic principles with international accounting standards. The proposed model offers insights for HEIs and policy makers by outlining the essential factors to be considered when integrating Islamic accounting education, positioning it as a competitive advantage for academic institutions.